PRIVATE CONSUMPTION IN THE EUROPEAN UNION: A COMPARATIVE STUDY - ONOFREI, Nicoleta; PAŞA, Adina Teodora (Economy and Sociology, 2021)
The aim of this paper is to study consumption of households from an economic and cultural perspective in the European Union with 28 Member States during the period 2010-2019. For this purpose, we compared the Eastern European countries, dominated by rapid economic growth and development with the Western European countries, which represent the most developed countries in the EU-28. From this perspective, we proposed a multidimensional analysis of consumption that includes macroeconomic indicators of households’ wealth, which strongly influence their consumption together with an overview on expenditure by consumption purpose. Moreover, we have also considered Hofstede’s cultural dimension theory based initially on four cultural dimensions (power distance, individualism versus collectivism, masculinity versus femininity, and uncertainty avoidance) to observe the impact national culture plays on households’ consumption in Eastern and Western European countries tracking the historical changes of these countries. Our methodological approach consisted in descriptive and inferential statistics based on the selected economic and cultural indicators. Pearson’s product-moment correlations were calculated to assess the correlations between the variables. Our analysis shows that the level of wealth is lower in Eastern European countries compared to Western Europe, which influences significantly the private consumption in these countries. Moreover, the systematic differences of national culture between Eastern and Western Europe influence strongly the private consumption of their population. Results of this paper indicate that in Eastern European countries the highest share of expenditure is allocated to primary needs such as food, non-alcoholic beverages, alcoholic beverages and cigarettes to the detriment of health, education, recreation and culture.